ENHANCED PRODUCTION LEVEL OF QUININE IN CELL SUSPENSION CULTURE OF Cinchona ledgeriana Moens BY PACLOBUTRAZOL - Diah Ratnadewi (SEAMEO BIOTROP, 2013)
Quinine is one of the major alkaloids in Cinchona spp., and it is used both as a medication and as a drink additive. The plant produces most of its alkaloids in the bark after 6â€“8 years of age.Repeated harvests can be performed until the plant dies, but only after every 3â€“5 years. We tested an improved method for culturing cell suspensions of Cinchona ledgerianato investigate the possibility of increasing production of quinine. The clone QRC 315 was treated with either a growth retardant (abscisic acid or paclobutrazol) or precursor feeding of L-tryptophan. To generate stress, we applied mannitol at 5.3 g/L combined with sucrose at a lower concentration (20 g/L),and we used sucrose at 30 g/L as the control. Paclobutrazol (7 mg/L) significantly suppressed cell growth and produced the highest level of quinine (11%) after 7 weeks of culture. L-tryptophan also reduced cell growth, but without any positive effect in the production of quinoline. The highest amount of quinine per culture flask, however, Â resulted in cells treated with 3 mg/L abscisic acid.